Polarizer and method for producing same
A polarized plate made with polyvinyl alcohol and boron compounds, optimized through specific manufacturing processes, addresses cracking issues and achieves neutral polarization and durability in organic EL display devices.
Patent Information
- Application Number
- JP2021007668
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-01-21
- Publication Date
- 2025-02-05
- Estimated Expiration
- 2041-01-21
AI Technical Summary
Conventional polarized plates used in organic EL display devices suffer from cracking due to severe temperature changes, particularly in applications like in-vehicle displays and outdoor digital signage, and fail to achieve neutral polarization and sufficient durability.
A polarized plate containing polyvinyl alcohol and boron compounds, with specific boron content, transmittance, and polarization values, manufactured through a process involving film extension, drying, and moist heat treatment to enhance durability and achieve neutral polarization.
The solution provides a polarized plate with sufficient optical performance, durability under severe temperature changes, and neutral polarization, suitable for organic EL display devices.
Smart Images

Figure 0007627120000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a polarizer and a method for producing the same. [Background technology]
[0002] Flat panel displays (FPDs) have grown from small devices such as calculators and wristwatches in the early stages of their development to a wide range of devices in recent years, such as laptop computers, monitors, color projectors, televisions, in-car navigation systems, mobile phones, and measuring instruments used both indoors and outdoors. In recent years, with the expansion into mobile applications, particularly in small laptop computers and mobile phones, there has been a demand for thinner polarizing plates.
[0003] Liquid crystal displays (LCDs) are widely used in FPDs, but in recent years, there has been an increase in demand for image display devices other than LCDs, particularly organic electroluminescence display devices (organic EL display devices), primarily for mobile applications. Organic EL display devices often use organic EL panels with anti-reflection capabilities, with a polarizing plate, especially an elliptical or circular polarizing plate, placed on the viewing side of the organic EL element. An elliptical or circular polarizing plate is formed by laminating a 1 / 4 wavelength retardation plate (i.e., a λ / 4 plate) on a linear polarizing plate so that the slow axes of both plates intersect at a specified angle.
[0004] A characteristic of polarizing plates used in OLED displays is their high transmittance. Polarizing plates for LCDs must have high polarization performance because they need to block light when displaying black, but since low transmittance for OLED applications leads to loss of display light, polarizing plates with higher transmittance than those used in LCDs are often used. On the other hand, the anti-reflection function required for OLED displays does not require the same high degree of polarization as the polarizing plates used in LCDs.
[0005] The polarizing plates used in these FPDs are made of a matrix (a stretched film oriented by uniaxial stretching) of polyvinyl alcohol resin (hereinafter sometimes abbreviated as "PVA") film, to which an iodine-based dye (I3- or I 5- In the mainstream, a protective film is attached to one or both sides of a polarizer to which a dichroic dye (such as a terpolymer) is adsorbed. This polarizer is produced by uniaxially stretching a PVA film that already contains a dichroic dye, by uniaxially stretching the PVA film and adsorbing the dichroic dye at the same time, or by uniaxially stretching the PVA film and then adsorbing the dichroic dye.
[0006] However, polarizing plates using PVA have the problem that they are prone to cracking when used in environments with drastic temperature changes, and this problem is more likely to be pronounced the thinner the polarizer is.
[0007] In response to this problem, a polarizing plate with improved heat cycle properties has been proposed in which a polarizing plate protective film containing a hydrogenated norbornene resin is attached to a polarizer (Patent Document 1).
[0008] In addition, focusing on the fact that cracks can also occur due to condensation that can occur during product use, a polarizing plate with improved crack resistance in environments in which the plate comes into contact with water has been proposed (Patent Document 2). The polarizing plate includes a polarizer and a functional layer laminated on at least one side of the polarizer, in which the elastic modulus of the polarizer in the polarizer transmission axis direction minus the elastic modulus of the functional layer in the polarizer transmission axis direction is -1100 MPa or more. [Prior art documents] [Patent documents]
[0009] [Patent Document 1] International Publication No. 2017 / 110342 [Patent Document 2] JP 2017-129859 A Summary of the Invention [Problem to be solved by the invention]
[0010] However, it has been found that in applications where organic EL display devices are exposed to more drastic temperature changes, such as in-vehicle displays and outdoor digital signage displays, which have been developed in recent years, the occurrence of cracks cannot be sufficiently suppressed even with the above-mentioned conventional technologies. This is because, in the case of high-transmittance polarizers for organic EL display devices, the iodine concentration in the polarizer is low, so the cross-linking effect of the iodine-based dye in the polarizer is small, resulting in lower durability and more susceptibility to cracking than polarizers for LCDs.
[0011] Furthermore, in recent years, there has been an increasing demand for polarizing plates with a neutral hue, without any yellow or blue tint, in order to suppress coloring during white display on FPDs and to ensure the design flexibility of color filters during panel design. However, it has become clear that it is difficult to obtain a polarizer with a neutral hue even when using the above-mentioned conventional techniques.
[0012] In other words, an object of the present invention is to provide a polarizer and a method for producing a polarizer that can produce a polarizing plate having sufficient optical performance even with a thin film thickness, excellent durability even in an environment with rapid temperature changes, and a neutral hue. [Means for solving the problem]
[0013] The present inventors have conducted extensive research to solve the above problems and have completed the present invention. That is, the present invention relates to the following [1] to [7]. [1] A polarizer containing polyvinyl alcohol and a boron compound, the total boron content in the polarizer being 1.0 to 3.5 mass%, the single transmittance of the polarizer being 45% or more, the degree of polarization of the polarizer being 85% or more, and the single b value of the polarizer being -1.0 to 0.8. [2] The polarizer according to [1], wherein the polarizer has a thickness of 20 μm or less. [3] A polarizing plate comprising the polarizer according to [1] or [2] laminated thereon. [4] An organic electroluminescence display device comprising the polarizing plate according to [3]. [5] A method for producing a polarizer, the method including: a stretching step of uniaxially stretching the polyvinyl alcohol film, the polyvinyl alcohol film being made of a polarizer; a drying step of heat-drying the stretched polyvinyl alcohol film; and a moist heat treatment step of holding the dried polyvinyl alcohol film under a tension of 400 to 1,000 N / m in the same stretching direction as in the stretching step in an atmosphere having a temperature of 50 to 80°C and a humidity of 65% RH or more for 0.5 to 4 hours. [6] The method for producing a polarizer according to [5], wherein the stretching temperature in the stretching treatment step is 55 to 65°C. [7] The method for producing a polarizer according to [5] or [6], wherein the polyvinyl alcohol film has a thickness of 60 μm or less, and the resulting polarizer has a thickness of 20 μm or less. Effect of the Invention
[0014] By using the polarizer of the present invention, a polarizing plate having sufficient optical performance even with a relatively thin film thickness, excellent durability even in an environment with drastic temperature changes, and a neutral hue can be obtained. Furthermore, the polarizer of the present invention can be suitably used in an organic EL display device. In addition, by employing the manufacturing method of the polarizer of the present invention, the above-mentioned excellent polarizer can be provided. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] The present invention will be described in detail below. In this specification, the upper and lower limits of numerical ranges (contents of each component, values calculated from each component, and each physical property, etc.) can be appropriately combined.
[0016] The polarizer of the present invention contains polyvinyl alcohol and a boron compound, and has a total boron element content in the polarizer of 1.0 to 3.5 mass %, a single transmittance of the polarizer of 45% or more, a degree of polarization of the polarizer of 85% or more, and a single b value of the polarizer of -1.0 to 0.8.
[0017] By setting the total boron element content in the polarizer to 1.0 to 3.5% by mass, the boric acid crosslinks are partially removed and the polarizer surface is softened while maintaining sufficient optical performance, so that the occurrence of cracks can be suppressed even in the state of a single-layer polarizer, and a polarizing plate laminated with a protective film also has excellent durability. In addition, by setting the single transmittance of the polarizer to 45% or more and the polarization degree of the polarizer to 85% or more, a polarizing plate that does not lose a lot of display light and fully exhibits anti-reflection function for use in an organic EL display device can be obtained. Furthermore, by setting the single b value of the polarizer to -1.0 to 0.8, a polarizer with a color close to neutral gray can be obtained, and a polarizing plate with a neutral hue can be obtained.
[0018] In the present invention, the polyvinyl alcohol (hereinafter, polyvinyl alcohol may be abbreviated as "PVA") may be one obtained by saponifying a polyvinyl ester obtained by polymerizing one or more vinyl esters such as vinyl acetate, vinyl formate, vinyl propionate, vinyl butyrate, vinyl pivalate, vinyl versatate, vinyl laurate, vinyl stearate, vinyl benzoate, and isopropenyl acetate. Among the above vinyl esters, compounds having a vinyloxycarbonyl group in the molecule are preferred, and vinyl acetate is more preferred, from the standpoints of ease of production of PVA, ease of availability, cost, and the like.
[0019] The polyvinyl ester is preferably one obtained by using only one or more kinds of vinyl esters as a monomer, and more preferably one obtained by using only one kind of vinyl ester as a monomer. However, within a range that does not significantly impair the effects of the present invention, the polyvinyl ester may be a copolymer of one or more kinds of vinyl esters with other monomers copolymerizable therewith.
[0020] Examples of other monomers copolymerizable with the vinyl esters include α-olefins having 2 to 30 carbon atoms, such as ethylene, propylene, 1-butene, and isobutene; (meth)acrylic acid or a salt thereof; (meth)acrylic acid esters such as methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, i-propyl (meth)acrylate, n-butyl (meth)acrylate, i-butyl (meth)acrylate, t-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, dodecyl (meth)acrylate, and octadecyl (meth)acrylate; (meth)acrylamide; N-methyl(meth)acrylamide, N-ethyl(meth)acrylamide, N,N-dimethyl(meth)acrylamide, diacetone(meth)acrylamide, (meth)acrylamidopropanesulfonic acid or a salt thereof, and (meth)acrylamidopropyldimethylamine or a salt thereof. Examples of the (meth)acrylamide derivatives include N-methylol (meth)acrylamide or its derivatives; N-vinylamides such as N-vinylformamide, N-vinylacetamide, and N-vinylpyrrolidone; vinyl ethers such as methyl vinyl ether, ethyl vinyl ether, n-propyl vinyl ether, i-propyl vinyl ether, n-butyl vinyl ether, i-butyl vinyl ether, t-butyl vinyl ether, dodecyl vinyl ether, and stearyl vinyl ether; vinyl cyanides such as (meth)acrylonitrile; vinyl halides such as vinyl chloride, vinylidene chloride, vinyl fluoride, and vinylidene fluoride; allyl compounds such as allyl acetate and allyl chloride; maleic acid or its salts, esters, or acid anhydrides; itaconic acid or its salts, esters, or acid anhydrides; vinyl silyl compounds such as vinyltrimethoxysilane; and unsaturated sulfonic acids or their salts. The polyvinyl esters may have structural units derived from one or more of the other monomers described above.
[0021] The proportion of the structural units derived from the other monomers in the polyvinyl ester is preferably 15 mol % or less, more preferably 10 mol % or less, and even more preferably 5 mol % or less, based on the number of moles of all structural units constituting the polyvinyl ester.
[0022] As the polyvinyl alcohol, one that has not been graft-copolymerized can be preferably used, but as long as the effect of the present invention is not significantly impaired, the polyvinyl alcohol may be modified with one or more graft-copolymerizable monomers. The graft copolymerization can be carried out on at least one of polyvinyl ester and polyvinyl alcohol obtained by saponifying the polyvinyl ester. Examples of the graft-copolymerizable monomer include unsaturated carboxylic acid or derivatives thereof; unsaturated sulfonic acid or derivatives thereof; and α-olefins having 2 to 30 carbon atoms. The proportion of structural units derived from graft-copolymerizable monomers in polyvinyl ester or PVA is preferably 5 mol% or less based on the number of moles of all structural units constituting polyvinyl ester or polyvinyl alcohol.
[0023] The polyvinyl alcohol may or may not be crosslinked at some of its hydroxyl groups, and may or may not react with an aldehyde compound such as acetaldehyde or butylaldehyde to form an acetal structure.
[0024] The degree of polymerization of the polyvinyl alcohol is not particularly limited, but is preferably 1,000 or more. When the degree of polymerization of the polyvinyl alcohol is 1,000 or more, the polarization performance of the obtained polarizer can be further improved. If the degree of polymerization of the polyvinyl alcohol is too high, it tends to lead to an increase in the production cost of the polyvinyl alcohol and poor processability during film formation, so the degree of polymerization of the polyvinyl alcohol is more preferably within the range of 1,000 to 10,000, even more preferably within the range of 1,500 to 8,000, and particularly preferably within the range of 1,800 to 4,000.
[0025] The degree of saponification of the above polyvinyl alcohol is preferably 95 mol % or more, more preferably 98 mol % or more, even more preferably 99 mol % or more, and particularly preferably 99.3 mol % or more, in order to improve the moist heat resistance of the resulting polarizer.
[0026] The polarizer of the present invention contains a boron compound, which can form a crosslinked structure and provide durability in a humid and hot environment.
[0027] The boron compound includes boric acid, borax and other borate salts, and these boron compounds may be used alone or in combination of two or more kinds.
[0028] Among these boron compounds, boric acid is preferred from the viewpoint of improving durability in a moist and hot environment.
[0029] The polarizer of the present invention has a total boron element content in the polarizer of 1.0 to 3.5% by mass with respect to the weight of the polarizer. If it is less than 1.0% by mass, durability in a humid and hot environment is significantly reduced. The total boron element content in the polarizer is preferably 2.0% by mass or more. On the other hand, if it is more than 3.5% by mass, many cracks are generated after a heat cycle test. The total boron element content in the polarizer is preferably 3.0% by mass or less. The heat cycle test will be described later.
[0030] The polarizer of the present invention has a single transmittance of 45% or more. In an organic EL display device, if the single transmittance of the polarizer is less than 45%, the screen of the flat panel display (FPD) becomes dark, so that the power consumption increases to ensure the brightness of the screen, and the life of the organic EL element is shortened. In a liquid crystal display device, if the single transmittance of the polarizer is 45% or more, the contrast ratio, which depends on the polarization degree of the polarizer, tends to decrease. The single transmittance of the polarizer is preferably 46% or more. On the other hand, the upper limit of the single transmittance of the polarizer is not particularly limited, but if the single transmittance is too high, the polarization degree may decrease and the polarizing function may not be sufficiently exhibited. Therefore, the single transmittance of the polarizer is preferably 49% or less, more preferably 48% or less. The method for measuring the single transmittance is as described below.
[0031] The degree of polarization of the polarizer of the present invention is 85% or more. If the degree of polarization is less than 85%, the polarizing function may not be sufficiently exhibited, and the antireflection function may be deteriorated. The degree of polarization of the polarizer is preferably 88% or more, more preferably 90% or more.
[0032] The single b value of the polarizer of the present invention is -1.0 to 0.8. The single hue refers to the hue of a single polarizer measured using a color difference meter, and the b value refers to a value expressing the hue in the CIE coordinate system, and the b value is calculated as b=200[(Y / Yn)1 / 3-(Z / Zn)1 / 3], where +b means yellow and -b means blue (where Yn and Zn correspond to Y and Z of the reference white hue). That is, the single b value refers to the b value in the CIE coordinate system obtained by measuring the hue of a single polarizer using a color difference meter. If the single b value is less than -1.0, the polarizer becomes too blue, and if it is 0.8 or more, the polarizer becomes too yellow, making it difficult to realize a neutral gray hue for the polarizer. Therefore, the single b value of the polarizer is preferably -0.5 to 0.5, and more preferably -0.2 to 0.3.
[0033] The polyvinyl alcohol film is a non-stretched film formed from a solution containing polyvinyl alcohol. The polarizer is a film having a polarizing property, which is produced by impregnating the polyvinyl alcohol film with a dichroic dye and stretching the film. Hereinafter, the polyvinyl alcohol film used in the polarizer of the present invention will be described. The polyvinyl alcohol film may be abbreviated as "PVA film".
[0034] The polyvinyl alcohol film may contain a plasticizer in addition to the above-mentioned polyvinyl alcohol and boron compound. By containing a plasticizer in the polyvinyl alcohol film, the handling property and stretchability of the polyvinyl alcohol film can be improved. As the plasticizer, a polyhydric alcohol is preferably used, and specific examples include ethylene glycol, glycerin, propylene glycol, diethylene glycol, diglycerin, triethylene glycol, tetraethylene glycol, and trimethylolpropane, and the polyvinyl alcohol film can contain one or more of these plasticizers. Among these, glycerin is preferred because it improves the stretchability of the polyvinyl alcohol film.
[0035] The content of the plasticizer in the polyvinyl alcohol film is preferably 2 to 20 parts by mass, more preferably 3 to 17 parts by mass, and even more preferably 4 to 14 parts by mass, per 100 parts by mass of polyvinyl alcohol. When the content of the plasticizer in the polyvinyl alcohol film is 2 parts by mass or more per 100 parts by mass of polyvinyl alcohol, the stretchability of the polyvinyl alcohol film is improved. On the other hand, when the content of the plasticizer in the polyvinyl alcohol film is 20 parts by mass or less per 100 parts by mass of polyvinyl alcohol, it is possible to suppress the plasticizer from bleeding out onto the surface of the polyvinyl alcohol film, which would otherwise cause a decrease in the handleability of the polyvinyl alcohol film.
[0036] When a polyvinyl alcohol film is produced using a film-forming solution containing polyvinyl alcohol, it is preferable to contain a surfactant in the film-forming solution, since this suppresses the occurrence of uneven thickness of the film and also facilitates peeling of the polyvinyl alcohol film from a metal roll or belt after film formation, thereby improving film formability. The type of surfactant contained in the film-forming solution, and therefore the surfactant contained in the polyvinyl alcohol film, is not particularly limited, but from the viewpoint of peelability from a metal roll or belt, anionic surfactants or nonionic surfactants are preferred, and nonionic surfactants are particularly preferred.
[0037] Suitable anionic surfactants include, for example, carboxylic acid types such as potassium laurate; sulfate ester types such as octyl sulfate; and sulfonic acid types such as dodecylbenzenesulfonate.
[0038] Suitable examples of nonionic surfactants include alkyl ether types such as polyoxyethylene oleyl ether; alkyl phenyl ether types such as polyoxyethylene octylphenyl ether; alkyl ester types such as polyoxyethylene laurate; alkyl amine types such as polyoxyethylene lauryl amino ether; alkyl amide types such as polyoxyethylene lauric acid amide; polypropylene glycol ether types such as polyoxyethylene polyoxypropylene ether; alkanolamide types such as lauric acid diethanolamide and oleic acid diethanolamide; and allyl phenyl ether types such as polyoxyalkylene allyl phenyl ether.
[0039] These surfactants can be used alone or in combination of two or more. do.
[0040] When the film-forming solution contains a surfactant, the content of the surfactant in the film-forming solution and therefore in the polyvinyl alcohol film is preferably within the range of 0.01 to 0.5 parts by mass, more preferably within the range of 0.02 to 0.3 parts by mass, per 100 parts by mass of polyvinyl alcohol contained in the film-forming solution or polyvinyl alcohol film. By making the content of the surfactant 0.01 parts by mass or more per 100 parts by mass of polyvinyl alcohol, the occurrence of defects can be suppressed and the peelability from the metal roll can be improved. On the other hand, by making the content of the surfactant 0.5 parts by mass or less per 100 parts by mass of polyvinyl alcohol, blocking of the film due to bleed-out of the surfactant can be suppressed, and the film can be handled stably.
[0041] The polyvinyl alcohol film may consist only of polyvinyl alcohol and a boron compound, or may further contain the above-mentioned plasticizer and / or surfactant, and may also contain other components such as antioxidants, antifreezing agents, pH adjusters, masking agents, color inhibitors, and oils, if necessary.
[0042] The content of polyvinyl alcohol in the entire polyvinyl alcohol film is preferably within a range of 50 to 100% by mass, more preferably within a range of 80 to 100% by mass, and further preferably within a range of 85 to 100% by mass.
[0043] The thickness of the polyvinyl alcohol film is not particularly limited, but is preferably 60 μm or less, and more preferably 50 μm or less. When the thickness of the polyvinyl alcohol film is 60 μm or less, a thin polarizer suitable for an organic EL display device can be obtained. On the other hand, the thickness is preferably 1 μm or more, and more preferably 3 μm or more, since the polarizer can be manufactured more smoothly. When the thickness of the polyvinyl alcohol film is 1 μm or more, the occurrence of cracks in the obtained polarizer can be suppressed.
[0044] There is no particular restriction on the shape of the polyvinyl alcohol film, but it is preferably a long film because it allows the polarizer to be continuously produced with good productivity. The length of the long film is not particularly limited and can be appropriately set depending on the application of the polarizer to be produced, and can be, for example, within the range of 5 to 20,000 m. There is no particular restriction on the width of the long film, and it can be, for example, 50 cm or more, but since wide polarizers have been required in recent years, it is preferably 1 m or more, more preferably 2 m or more, and even more preferably 4 m or more. There is no particular restriction on the upper limit of the width of the long film, but if the width is too wide, it tends to be difficult to uniformly stretch the film when a polarizer is produced using a practical device, so the width of the polyvinyl alcohol film is preferably 7 m or less.
[0045] The method for producing the polyvinyl alcohol film is not particularly limited, and a method that makes the thickness and width of the film more uniform after film formation can be preferably adopted. For example, the polyvinyl alcohol film can be produced using a film-forming stock solution in which the above-mentioned polyvinyl alcohol and boron compound that constitute the polyvinyl alcohol film, and one or more of plasticizers, surfactants, and other components as necessary are dissolved in a liquid medium, or a film-forming stock solution that contains polyvinyl alcohol and a boron compound, and one or more of plasticizers, surfactants, other components, and liquid media as necessary, and in which polyvinyl alcohol is melted. When the film-forming stock solution contains at least one of plasticizers, surfactants, and other components, it is preferable that these components are uniformly mixed.
[0046] Examples of the liquid medium used to prepare the film-forming solution include water, dimethyl sulfoxide, dimethylformamide, dimethylacetamide, N-methylpyrrolidone, ethylene glycol, glycerin, propylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, trimethylolpropane, ethylenediamine, diethylenetriamine, etc., and one or more of these may be used. Among these, water is preferred from the viewpoints of its small environmental impact and ease of recovery.
[0047] The volatile fraction of the film-forming solution (the content in the film-forming solution of volatile components such as liquid medium removed by volatilization or evaporation during film formation) varies depending on the film-forming method, film-forming conditions, etc., but is preferably in the range of 50 to 95 mass%, more preferably in the range of 55 to 90 mass%, and even more preferably in the range of 60 to 85 mass%. When the volatile fraction of the film-forming solution is 50 mass% or more, the viscosity of the film-forming solution does not become too high, filtration and degassing during preparation of the film-forming solution are smoothly performed, and it becomes easy to produce a polyvinyl alcohol film with few foreign matter and defects. On the other hand, when the volatile fraction of the film-forming solution is 95 mass% or less, the concentration of the film-forming solution does not become too low, and it becomes easy to industrially produce a polyvinyl alcohol film.
[0048] The film-forming method when forming a polyvinyl alcohol film using the film-forming solution described above includes, for example, a cast film-forming method, an extrusion film-forming method, a wet film-forming method, and a gel film-forming method, and the cast film-forming method and the extrusion film-forming method are preferred. These film-forming methods may be used alone or in combination of two or more. Among these film-forming methods, the cast film-forming method and the extrusion film-forming method are more preferred because they can obtain a polyvinyl alcohol film with uniform thickness and width and good physical properties. The polyvinyl alcohol film can be dried or heat-treated as necessary.
[0049] The polyvinyl alcohol film is preferably heat-treated for the purpose of improving the productivity in the manufacturing process of the polarizer, etc. The heat treatment is one of the methods for adjusting the swelling degree and softening point of the polyvinyl alcohol film, which are measured by the following method.
[0050] [Swelling degree of PVA film] A rectangular sample measuring 10 cm in width and 20 cm in length was cut out from the PVA film to be measured, and this sample was further cut into a strip measuring 2 to 3 mm in width and 20 cm in length. Then, all of these strip samples were immersed in 1,000 g of distilled water at 30 ° C. After immersion for 30 minutes, the strip samples were taken out and centrifuged for 5 minutes at 3,000 rpm using a centrifuge (KOKUSAN XEM-KL-5886), and the mass "N" after dehydration (total of all strip samples) was measured. Next, the strip samples were dried in a dryer at 105 ° C. for 16 hours, and the mass "M" (total of all strip samples) was measured, and the swelling degree was calculated by the formula: swelling degree (%) = 100 × N / M. The same measurement was performed three times, and the average value was used.
[0051] [Softening point of PVA film] The softening point of the PVA film to be measured was measured using an automatic softening point measuring device "EX-820" manufactured by Daiichi Rika Co., Ltd. Specifically, a square sample with a size of 3 cm square was cut out from the PVA film, and this sample was sandwiched between a 3 cm square stainless steel plate with a 1 mm thickness and a 1 cm diameter circular hole in the center and a 3 cm square stainless steel plate with a 1 cm × 2 cm rectangular hole in the center, and the stainless steel plate with the circular hole was placed on a stand with the stainless steel plate with the circular hole facing up, and a steel ball (nominal: 3 / 8 (diameter 9.525 mm), grade: G60, mass: 3.5 g ± 0.05 g) as specified in JIS B1501:2009 was placed on the film located at the center of the circular hole. Then, 750 mL of distilled water at 25 ° C was added, and the temperature was raised at 5 ° C per minute, and the temperature when the film dropped to a position 25 mm from the stand was taken as the softening point of the PVA film.
[0052] The swelling degree of the PVA film used in the production of the polarizer of the present invention is preferably in the range of 160 to 240%, more preferably in the range of 170 to 230%, and particularly preferably in the range of 180 to 220%. When the swelling degree is 160% or more, it is possible to suppress the crystallization from proceeding excessively, and the film can be stably stretched to a high magnification. On the other hand, when the swelling degree is 240% or less, dissolution during stretching is suppressed, and the film can be stretched even under higher temperature conditions. The film of the present invention has a softening point of 63°C or less. This allows the production of an optical film with excellent shrinkage reduction. The softening point is preferably 60°C or less, more preferably 57°C or less, and even more preferably 55°C or less. The lower the softening point, the lower the shrinkage force of the optical film obtained. On the other hand, from the viewpoint of processability during use, such as when the film is uniaxially stretched, the industrial lower limit of the softening point is about 50°C.
[0053] Furthermore, the polarizer of the present invention exhibits sufficient crack resistance in a polarizing plate having a protective film bonded to both sides or one side of the polarizer, since the number of cracks generated after a heat cycle test (hereinafter sometimes abbreviated as heat cycle test) performed in accordance with the following procedures (A) to (D) is 25 or less per 7.5 cm width. (A) The polarizer is conditioned at a temperature of 23° C. and a humidity of 50 RH% for 18 hours, and then four film pieces measuring 10 cm in the length direction and 7.5 cm in the width direction are taken from the polarizer. (B) An adhesive sheet cut to 20 cm x 30 cm is attached to a 30 cm x 21 cm glass plate, and the four film pieces are attached to the four positions at the top right, top left, bottom right, and bottom left. (C) The glass plate to which the film piece was attached was subjected to a heat cycle of 200 cycles, in which one cycle was held at -40°C for 30 minutes and then at 85°C for 30 minutes. (D) After repeating the heat cycle 200 times, the total number of cracks occurring in the four film pieces over the entire length direction (10 cm) is counted and this is defined as the number of cracks per 7.5 cm width. The number of cracks generated after the heat cycle test is preferably 25 or less per 7.5 cm width, more preferably 20 or less per 7.5 cm width, and even more preferably 15 or less per 7.5 cm width. On the other hand, there is no particular lower limit on the number of cracks generated after the heat cycle test, but in the case of a polarizer with an extremely small number of cracks, the production cost is expected to be high, so that the number is preferably 5 or more per 7.5 cm width, and more preferably 10 or more per 7.5 cm width.
[0054] The thickness of the polarizer of the present invention is not particularly limited, but even if the thickness is 20 μm or less, a polarizing plate having sufficient optical performance, excellent durability even in an environment with rapid temperature changes, and a neutral hue can be obtained.
[0055] A polarizing plate formed by laminating the polarizer of the present invention can be used in liquid crystal displays and organic EL displays. In these applications, a polarizing plate formed by laminating the polarizer of the present invention and a protective film is a preferred embodiment of the present invention. A polarizing plate using the polarizer of the present invention has excellent durability, polarization performance, and hue, and is therefore suitable for use in organic EL displays, particularly organic EL displays for mobile devices.
[0056] The protective film is not particularly limited as long as it is optically transparent and has mechanical strength, and examples thereof include cellulose triacetate (TAC) film, cellulose acetate butyrate (CAB) film, acrylic film, polyester film, and cyclic olefin (COP) film. The polarizing plate may be one in which the protective film is bonded to one side of the polarizer, or one in which the protective film is bonded to both sides of the polarizer. Examples of adhesives for bonding include PVA adhesives, urethane adhesives, and ultraviolet-curing adhesives.
[0057] The method for producing the polarizer of the present invention will now be described. By employing the method for producing the polarizer of the present invention, the polarizer of the present invention can be produced efficiently.
[0058] The method for producing a polarizer of the present invention is a method for producing a polarizer, in which a polarizer is made of a polyvinyl alcohol film, and the method includes a stretching step of uniaxially stretching the polyvinyl alcohol film, a drying step of heat-drying the stretched polyvinyl alcohol film, and a moist heat treatment step of holding the dried polyvinyl alcohol film under a state in which a tension of 400 to 1000 N / m is applied in the same stretching direction as in the stretching step, in an atmosphere at a temperature of 50 to 80°C and a humidity of 65% RH or more for 0.5 to 4 hours.
[0059] In the method for producing a polarizer of the present invention, it is preferable to subject the raw PVA film to a swelling treatment (hereinafter, sometimes referred to as a "swelling treatment step") in advance before subjecting it to each step. In addition to the dyeing treatment step and the stretching treatment step, it is also preferable to subject the PVA film to a treatment for crosslinking the film using a crosslinking agent (hereinafter, sometimes referred to as a "crosslinking treatment step"), followed by a drying treatment and then a wet heat treatment. Before the drying treatment, a treatment for washing the PVA film (washing treatment) may be appropriately performed. In addition, in the method for producing a polarizer of the present invention, one type of treatment may be performed multiple times. Furthermore, multiple treatments may be performed simultaneously in one bath.
[0060] The method for producing a polarizer of the present invention is preferably a method in which a dyeing treatment step, a stretching treatment step, a drying treatment step, and a moist heat treatment step are performed in this order, more preferably a method in which a dyeing treatment step, a crosslinking treatment step, a stretching treatment step, a drying treatment step, and a moist heat treatment step are performed in this order, and further preferably a method in which a swelling treatment step, a dyeing treatment step, a crosslinking treatment step, a stretching treatment step, a drying treatment step, and a moist heat treatment step are performed in this order. Each step will be described in detail below.
[0061] The swelling treatment in the swelling treatment step can be performed by immersing the PVA film in water. The temperature of the water during immersion is preferably within the range of 20 to 40°C, more preferably within the range of 22 to 38°C, and even more preferably within the range of 25 to 35°C. The time for immersion in water is, for example, preferably within the range of 0.1 to 5 minutes, and more preferably within the range of 0.5 to 3 minutes. The water used during immersion in water is not limited to pure water, and may be an aqueous solution in which various components are dissolved, or a mixture of water and an aqueous medium.
[0062] The dyeing process in the dyeing step may be performed at any stage before, during, or after the stretching process, but is preferably performed before the stretching process. Dyeing is generally performed using an iodine-based dye by immersing the PVA film in a solution (particularly an aqueous solution) containing iodine and potassium iodide as a dye bath, and such a dyeing method is preferably used in the present invention. The iodine concentration in the dye bath is preferably within the range of 0.01 to 0.5% by mass, and the potassium iodide concentration is preferably within the range of 0.01 to 10% by mass. The temperature of the dye bath is preferably 20 to 50°C, particularly 25 to 40°C.
[0063] The crosslinking treatment in the crosslinking treatment step is a treatment in which the PVA film is immersed in an aqueous solution containing a crosslinking agent. The crosslinking treatment introduces a crosslinked structure into the PVA film, and when a stretching treatment is performed at a relatively high temperature in a wet state, it is possible to effectively prevent the PVA from dissolving into water. From this viewpoint, the crosslinking treatment is preferably performed after the dyeing treatment. As the crosslinking agent, one or more kinds of boron compounds such as boric acid and borax or other borates can be used. The concentration of the crosslinking agent in the aqueous solution containing the crosslinking agent is preferably within the range of 1 to 15% by mass, more preferably within the range of 2 to 7% by mass. The aqueous solution containing the crosslinking agent may contain an auxiliary such as potassium iodide. The temperature of the aqueous solution containing the crosslinking agent is preferably within the range of 20 to 50°C, more preferably within the range of 25 to 40°C.
[0064] The stretching treatment in the stretching treatment step may be performed by either a wet stretching method or a dry stretching method. In the wet stretching method, uniaxial stretching can be performed in an aqueous solution containing boric acid, or in the dye bath described above or in a fixing treatment bath described below. In the dry stretching method, uniaxial stretching can be performed in the atmosphere using the PVA film after water absorption. Among these, the stretching treatment is preferably a wet stretching method, and more preferably a wet stretching method in which uniaxial stretching is performed in an aqueous solution containing boric acid. The concentration of boric acid in the aqueous boric acid solution is preferably in the range of 0.5 to 6.0 mass%, more preferably in the range of 1.0 to 5.0 mass%, and particularly preferably in the range of 1.5 to 4.0 mass%. In addition, the aqueous boric acid solution may contain potassium iodide, and the concentration is preferably in the range of 0.01 to 10 mass%.
[0065] The stretching temperature in the stretching treatment is preferably within the range of 55 to 65°C.
[0066] From the viewpoint of the polarization performance of the resulting polarizer, the stretching ratio in the stretching treatment is preferably 5 times or more, more preferably 5.5 times or more, and particularly preferably 6 times or more. There is no particular upper limit to the stretching ratio, but the stretching ratio is preferably 8 times or less.
[0067] In the method for producing a polarizer of the present invention, a treatment for washing the PVA film (washing treatment) may be performed as appropriate. However, since the adsorption of the dye (iodine, etc.) to the PVA film can be strengthened, it is preferable to perform the washing treatment before the drying treatment step. As a washing treatment bath used for the washing treatment, an aqueous solution containing one or more boron compounds such as boric acid and borax can be used. If necessary, an iodine compound or a metal compound may be added to the washing treatment bath. In this case, the concentration of the boron compound in the washing treatment bath is preferably 1 to 15 mass %. When potassium iodide is contained in the aqueous solution, the concentration is preferably 0.01 to 10 mass %. The temperature of the washing treatment bath is preferably 15 to 60°C, particularly 20 to 40°C.
[0068] The drying process in the drying step is preferably carried out at a temperature of 30 to 150°C, and more preferably at 50 to 130°C.
[0069] In the wet heat treatment step, the PVA film that has passed through the drying treatment step is treated in an atmosphere with a temperature of 50 to 80°C and a humidity of 65% RH or more under a tension of 400 to 1000 N / m in the stretching direction. The tension is preferably 450 to 800 N / m, and more preferably 500 to 600 N / m. Although it is not clear why this treatment is able to reduce the number of cracks that occur after a heat cycle test, it is presumed that this is because, under high temperature and high humidity conditions, the boric acid crosslinks on the surface or inside of the PVA film are partially hydrolyzed, making the film surface more likely to soften and suppressing the occurrence of cracks.
[0070] The wet heat temperature in the wet heat treatment is preferably 55° C. or higher, more preferably 60° C. or higher, in order to cause hydrolysis of boric acid crosslinks with a sufficient amount of water vapor, and is preferably 75° C. or lower, more preferably 70° C. or lower, in order to suppress deterioration of optical properties.
[0071] The humidity in the wet heat treatment is preferably 70% RH or higher, more preferably 75% RH or higher, in order to cause hydrolysis of boric acid crosslinks with a sufficient amount of water vapor. On the other hand, if the humidity is too high, there is a concern that condensation will occur in the treatment zone and that the film will be contaminated by condensed water, so the humidity is preferably 90% RH or lower, more preferably 85% RH or lower.
[0072] The wet heat treatment time is preferably 1 hour or more, more preferably 1.5 hours or more, in order to sufficiently hydrolyze the boric acid crosslinks, and is preferably 3 hours or less, more preferably 2.5 hours or less, since a too long time may cause deterioration of optical properties.
[0073] By employing the polarizer manufacturing method of the present invention, and further by setting the thickness of the polyvinyl alcohol film to 60 μm or less and the thickness of the obtained polarizer to 20 μm or less, it is possible to obtain a thin-film polarizer having improved flexibility and reduced shrinkage force, which can be applied to organic EL display devices, particularly organic EL display devices for mobile devices.
[0074] The present invention will now be described in more detail with reference to examples.
[0075] [Evaluation of optical performance of polarizers] A rectangular film piece measuring 3 cm in the length direction and 1.5 cm in the width direction was taken from the center of the polarizer obtained in each Example or Comparative Example. Using a spectrophotometer with an integrating sphere ("V7100" manufactured by JASCO Corporation), the single transmittance, polarization degree, and single b value of the film piece were measured after luminosity correction in accordance with JIS Z8722 (measurement method for object color).
[0076] [Calculation of total boron element content (mass%) in polarizer] The polarizers obtained in each Example or Comparative Example were conditioned at a temperature of 23°C and a humidity of 50%RH for 16 hours, and then a sample of about 1 mg was taken and its mass (J(g)) was measured. Next, the taken sample was dissolved in 20 mL of distilled water to prepare an aqueous solution. This aqueous solution was used as a measurement sample, and its mass (K(g)) was measured. Then, the boron concentration (L(ppm)) of the measurement sample was measured using a Shimadzu Corporation multi-type ICP emission spectrometer (ICPE-9000). Then, the value calculated by substituting the value into the following calculation formula was taken as the total boron element content (mass%) in the polarizer. Total boron content in polarizer (mass%) =[(L×10 -6 ×K) / J]×100
[0077] [Evaluation of the number of cracks] The polarizer obtained in each Example or Comparative Example was conditioned at 23°C and 50 RH% for 18 hours, and then four pieces of film measuring 10 cm in length and 7.5 cm in width were cut out from the polarizer. Next, a 20 cm x 30 cm piece of adhesive (Mitate Imaging Co., Ltd., MCS70, thickness 25 μm) was attached to a 30 cm x 21 cm glass plate, and the above four pieces of film were attached to the four positions at the upper right, upper left, lower right, and lower left to obtain a measurement sample. Using a thermal shock tester (ETAC WINTECH NT530A) manufactured by Kusumoto Chemical Co., Ltd., a cycle of holding at a temperature of -40°C for 30 minutes and then holding at a temperature of 85°C for 30 minutes was repeated 200 cycles. The total number of cracks occurring in the four pieces of film over the entire length direction (10 cm) after 200 cycles was counted.
[0078] [Example 1] A film-forming stock solution with a volatile content of 66% by mass consisting of 100 parts by mass of polyvinyl alcohol (saponified vinyl acetate homopolymer, polymerization degree 2,800, saponification degree 99.3 mol%), 10 parts by mass of glycerin as a plasticizer, 0.1 parts by mass of sodium polyoxyethylene lauryl ether sulfate as a surfactant, and water was used to continuously form a long PVA film with a thickness of 45 μm, a swelling degree of 203%, and a softening point of 67.9°C using a film-forming device equipped with 18 drying rolls whose rotating axes are parallel to each other.
[0079] Specifically, the above film-forming stock solution was extruded from a T-shaped slit die onto a first drying roll (surface temperature 93°C, peripheral speed 13.6 m / min) in the form of a film, and dried on the first drying roll while hot air (temperature 90°C, dew point temperature 10°C) was uniformly blown onto the entire non-contact surface of the first drying roll at a wind speed of 5 m / sec until the volatile content of the polyvinyl alcohol film reached 25% by mass. The film was then peeled off from the first drying roll (the volatile content when peeled off from the first drying roll was 25% by mass), and dried with the second drying roll and subsequent drying rolls so that the first drying roll contact surface and the first drying roll non-contact surface of the PVA film alternately faced each drying roll. Furthermore, both ends (edges) in the width direction were cut and removed, and the film was then wound into a roll to obtain the above polyvinyl alcohol film.
[0080] A sample of 5 cm wide x 9 cm long was cut from the center of the width direction of the obtained polyvinyl alcohol film so that a range of 5 cm wide x 5 cm long could be uniaxially stretched. This sample was uniaxially stretched in the length direction to twice its original length (first-stage stretching) while immersed in water with a liquid temperature of 30°C for 1 minute and swollen (swelling treatment). Next, while immersed in an iodine aqueous solution (dyeing bath: iodine concentration 0.019 mass%, potassium iodide concentration 0.44 mass%) with a liquid temperature of 32°C for 2 minutes, it was dyed while uniaxially stretched in the length direction to 1.3 times (total 2.5 times) (second-stage stretching) (dyeing treatment). Next, while immersed in an aqueous boric acid solution (crosslinking bath: boric acid concentration 2.6 mass%) with a liquid temperature of 32°C for 2 minutes, it was crosslinked while uniaxially stretched in the length direction to 1.2 times (total 3.0 times) (third-stage stretching) (crosslinking treatment). Next, the film was uniaxially stretched in the length direction by 2.0 times (total 6.0 times) while immersed in a boric acid / potassium iodide aqueous solution (stretching bath: boric acid concentration 2.8% by mass, potassium iodide concentration 5.0% by mass) at a liquid temperature of 58°C (4th stage stretching) (stretching treatment). Next, the film was washed by immersing in a potassium iodide aqueous solution (washing bath: boric acid concentration 1.5% by mass, potassium iodide concentration 3.3% by mass) at a liquid temperature of 22°C for 10 seconds without stretching (washing treatment). Next, the film was dried for 90 seconds in a dryer at 80°C with both ends fixed so that dimensional change did not occur in the length direction (drying treatment). After that, the film was held for 4 hours in a thermo-hygrostat maintained at a temperature of 60°C and a humidity of 90%RH with a tension of 500N / m applied in the length direction (humid heat treatment). The polarizer thus obtained was subjected to measurements of the single transmittance, the polarization degree, the single b value, the total boron element content, and the number of cracks by the methods described above. The results are shown in Table 1.
[0081] [Example 2] A polarizer was produced in the same manner as in Example 1, except that the time for keeping in the thermostatic chamber in the wet heat treatment was changed to 0.5 hours. The single transmittance, polarization degree, single b value, total boron element content, and number of cracks of the obtained polarizer were measured by the above-mentioned methods. The results are shown in Table 1.
[0082] [Example 3] A polarizer was produced in the same manner as in Example 1, except that the time for keeping in the thermostatic chamber in the wet heat treatment was changed to 2 hours. The single transmittance, polarization degree, single b value, total boron element content, and number of cracks of the obtained polarizer were measured by the above-mentioned methods. The results are shown in Table 1.
[0083] [Example 4] A polarizer was produced in the same manner as in Example 1, except that the temperature in the wet heat treatment was changed to 50° C. For the obtained polarizer, the single transmittance, the polarization degree, the single b value, the total boron element content, and the number of cracks were measured by the above-mentioned methods. The results are shown in Table 1.
[0084] [Example 5] A polarizer was produced in the same manner as in Example 1, except that the humidity in the wet heat treatment was changed to 70% RH. The single transmittance, polarization degree, single b value, total boron element content, and number of cracks of the obtained polarizer were measured by the above-mentioned methods. The results are shown in Table 1.
[0085] [Example 6] A polarizer was produced in the same manner as in Example 1, except that the liquid temperature of the boric acid / potassium iodide aqueous solution (stretching bath) used in the stretching treatment (fourth stage stretching) was changed to 62°C, and the time for which the film was held in the thermostatic chamber in the wet heat treatment was changed to 0.5 hours. The single transmittance, polarization degree, single b value, total boron element content, and number of cracks of the obtained polarizer were measured by the above-mentioned methods. The results are shown in Table 1.
[0086] [Example 7] A triacetate cellulose (TAC) film with PVA glue (PVA content: 3% by mass) applied on one side was placed on both sides of the polarizer obtained in Example 1 and laminated, and then dried at 60° C. for 10 minutes to produce a polarizing plate. The obtained polarizing plate had sufficient durability with no cracks observed.
[0087] [Comparative Example 1] A polarizer was produced in the same manner as in Example 1, except that the time for which the polarizer was kept in the thermostatic chamber in the moist heat treatment was changed to 8 hours. The single transmittance, degree of polarization, single b value, total boron element content, and number of cracks were measured for the obtained polarizer by the above-mentioned methods. The results are shown in Table 1. However, the polarizing plate produced in the same manner as in Example 7, except that the polarizer used for lamination was changed to the above-mentioned polarizer, had a low degree of polarization, did not have sufficient polarization performance, and did not have a sufficient hue.
[0088] [Comparative Example 2] A polarizer was produced in the same manner as in Example 1, except that the iodine concentration of the iodine aqueous solution (dyeing bath) used in the dyeing treatment (second-stage stretching) was changed to 0.052 mass%, the potassium iodide concentration was changed to 1.2 mass%, and the time of holding in the thermostatic chamber in the moist heat treatment was changed to 6 hours. The single transmittance, polarization degree, single b value, total boron element content, and number of cracks of the obtained polarizer were measured by the above-mentioned methods. The results are shown in Table 1. However, the polarizing plate produced in the same manner as in Example 7, except that the polarizer used for lamination was changed to the above-mentioned polarizer, had low transmittance and did not have sufficient polarization performance.
[0089] [Comparative Example 3] A polarizer was produced in the same manner as in Example 1, except that the temperature in the wet heat treatment was changed to 40° C. For the obtained polarizer, the single transmittance, degree of polarization, single b value, total boron element content, and number of cracks were measured by the above-mentioned methods. The results are shown in Table 1. However, a polarizing plate produced in the same manner as in Example 7, except that the polarizer used for lamination was changed to the above-mentioned polarizer, did not have sufficient durability.
[0090] [Comparative Example 4] A polarizer was produced in the same manner as in Example 1 except that the temperature in the wet heat treatment was changed to 90° C. However, the polarizer shrunk during the wet heat treatment, and therefore, the polarizer could not be obtained.
[0091] [Comparative Example 5] A polarizer was produced in the same manner as in Example 1, except that the time for which the film was kept in the thermostatic chamber in the moist heat treatment was changed to 0.5 hours, and that the temperature and humidity in the moist heat treatment were changed to 60°C and 50% RH. The single transmittance, polarization degree, single b value, total boron element content, and number of cracks were measured for the obtained polarizer by the above-mentioned methods. The results are shown in Table 1. However, the polarizing plate produced in the same manner as in Example 7, except that the polarizer used for lamination was changed to the above-mentioned polarizer, did not have a sufficient hue.
[0092] [Comparative Example 6] A polarizer was produced in the same manner as in Example 1, except that the liquid temperature of the boric acid / potassium iodide aqueous solution (stretching bath) used in the stretching treatment (fourth stage stretching) was changed to 50°C. However, the polarizer was hard and cracked during the wet heat treatment, so no polarizer could be obtained.
[0093] [Comparative Example 7] A polarizer was produced in the same manner as in Example 1, except that the liquid temperature of the boric acid / potassium iodide aqueous solution (stretching bath) used in the stretching treatment (fourth stage stretching) was changed to 70°C. However, the polarizer melted during the stretching treatment (fourth stage stretching), and therefore the polarizer could not be obtained.
[0094] [Comparative Example 8] A polarizer was produced in the same manner as in Example 1, except that the boric acid concentration of the boric acid / potassium iodide aqueous solution (stretching bath) used in the stretching treatment (fourth-stage stretching) was changed to 3.5% by mass, and the time for which the film was held in the thermostatic chamber in the moist heat treatment was changed to 0.5 hours. The single transmittance, polarization degree, single b value, total boron element content, and number of cracks of the obtained polarizer were measured by the above-mentioned methods. The results are shown in Table 1. However, the polarizing plate produced in the same manner as in Example 7, except that the polarizer used for lamination was changed to the above-mentioned polarizer, did not have sufficient durability.
[0095] [Comparative Example 9] A polarizer was produced in the same manner as in Example 1, except that the tension in the wet heat treatment was changed to 300 N / m. The single transmittance, polarization degree, single b value, total boron element content, and number of cracks of the obtained polarizer were measured by the above-mentioned methods. The results are shown in Table 1. However, a polarizing plate produced in the same manner as in Example 7, except that the polarizer used for lamination was changed to the above-mentioned polarizer, did not have sufficient durability.
[0096] [Comparative Example 10] A polarizer was produced in the same manner as in Example 1 except that the tension in the wet heat treatment was changed to 1200 N / m. However, the polarizer broke during the wet heat treatment, and therefore the polarizer could not be obtained.
[0097] [Table 1]
Claims
1. A polarizer containing polyvinyl alcohol and a boron compound, the polarizer having a total boron element content of 1.0 to 3.5 mass %, a single transmittance of the polarizer being 45% or more, a degree of polarization of the polarizer being 85% or more, a single b value of the polarizer being -1.0 to 0.8, and the number of cracks generated after a heat cycle test performed in accordance with the following procedures (A) to (D) being 20 or less per 7.5 cm width. (A) A polarizer is conditioned at a temperature of 23° C. and a humidity of 50% RH for 18 hours, and then four film pieces each having a length of 10 cm and a width of 7.5 cm are taken from the polarizer. (B) An adhesive sheet cut to 20 cm x 30 cm is attached to a 30 cm x 21 cm glass plate, and the four film pieces are attached to the four positions at the top right, top left, bottom right, and bottom left. (C) The glass plate to which the film piece was attached was subjected to a heat cycle of 200 cycles, the cycle consisting of holding the glass plate at -40°C for 30 minutes and then holding the plate at 85°C for 30 minutes. (D) After repeating the heat cycle 200 times, the total number of cracks occurring in the four film pieces over the entire length direction (10 cm) is counted and this is defined as the number of cracks per 7.5 cm width.
2. The polarizer according to claim 1 , wherein the polarizer has a thickness of 20 μm or less.
3. A polarizing plate comprising the polarizer according to claim 1 or 2 laminated thereon.
4. An organic electroluminescence display device comprising the polarizing plate according to claim 3 .
5. 2. The method for producing a polarizer according to claim 1, wherein the polarizer is made of a polyvinyl alcohol film, the method comprising: a stretching treatment step of uniaxially stretching the polyvinyl alcohol film; a drying treatment step of heating and drying the stretched polyvinyl alcohol film; and a moist heat treatment step of holding the dried polyvinyl alcohol film in a state in which a tension of 400 to 1000 N / m is applied in the same stretching direction as in the stretching treatment step, in an atmosphere at a temperature of 50 to 80° C. and a humidity of 65% RH or more for 0.5 to 4 hours.
6. The method for producing a polarizer according to claim 5, wherein the stretching temperature in the stretching treatment step is 55 to 65°C.
7. The method for producing a polarizer according to claim 5 or 6, wherein the polyvinyl alcohol film has a thickness of 60 μm or less, and the obtained polarizer has a thickness of 20 μm or less.
Citation Information
Patent Citations
Polarizing plates and liquid crystal display devices
JP2008529038A
Polarizing film and manufacturing method thereof and polarizer
JP2013148806A
Polarizing film, polarizing plate, and liquid crystal panel
JP2015222368A
Polarizing plate and image display device
JP2017129859A
Polarizing plate and image display device
JP2017204003A